Development of a contact and a material model of laminated stacks - Luchscheider, Vera; Willner, Kai; Maidorn, Mischa (Proceeding 3rd International Electric Drives Production Conferenz, 2013)
The paper presents measurements and simulations of the stiffness of lamination stacks, which is a relevant parameter for the construction of electric machines. Since the progressive stiffness behavior of a lamination stack is dominated by the contact between the single sheets, different contact models are presented, where the selection and combination of the contact models is based on experimental tests on simple stacks of typical sheet material. With the help of the contact models, a material model will be created using the method of multiscales. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-TM.develo_5
Keywords: contact behavior; hysteresis; lamination stack